(untitled) (IJM: Journal of Multidisiplinary, 2024)
Schizophrenia manifests through positive symptoms, such as hallucinations, where individuals perceive sensations only discernible to them. These hallucinations can profoundly impact self-control, underscoring the importance of effective strategies to manage and mitigate the impacts. One promising avenue is the implementation of individual occupational therapy, selected for its calming influence and capacity to bolster self-confidence. This case study focused on the application of individual occupational therapy to patients experiencing auditory hallucinations at Balee Seulanga Room of Aceh Mental Hospital. The chosen intervention was the individual occupational therapy. The rationale behind incorporating occupational therapy was its ability to instill a sense of tranquility while fostering increased self-assurance. Upon conducting the intervention, the findings revealed a notable reduction in both the duration and frequency of hallucinations, ultimately leading to a heightened state of relaxation for the patients. The findings derived from this case study underscored the efficacy of occupational therapy in alleviating signs and symptoms associated with auditory hallucinations. Furthermore, it also highlighted the therapy's potential to enhance patients' abilities and promote adaptive behaviors. In conclusion, this case study suggests the continued integration of occupational therapy as part of comprehensive treatment plans for individuals grappling with schizophrenia. Beyond the confines of the hospital, the hope is that patients can perpetuate these therapeutic practices independently, fostering a sense of autonomy and productivity in their daily lives.